Decreased REG1α expression suppresses growth, invasion and angiogenesis of bladder cancer. Issue 4 (April 2017) - Geng, J.; Fan, J.; Wang, Q.; Zhang, X.-P.; Kang, L.; Li, Q.-Y.; Xu, Y.-F.; Peng, B.; Zheng, J.-H.; Yao, X.-D.
Abstract: Background: Previous study has indicated association between REG1α and bladder cancer. The aim of this study was to investigate the role of Regenerating gene I alpha (REG1α) in bladder cancer. Methods: The role of REG1α in bladder cancer cell proliferation, migration and VEGF-induced angiogenesis was explored in vitro and in vivo . Immunohistochemistry (IHC) analysis was assessed to determine the expression of REG1α in ten paired bladder cancer and adjacent non-cancerous tissues, and in 296 bladder cancer samples. Results: Down-regulation of REG1α expression significantly reduced the proliferation, migration, invasion and VEGF-induced angiogenesis in vitro and the growth of xenograft tumors in vivo . VEGF expression in bladder cancer is associated with REG1α expression and recurrence. REG1α was overexpressed in bladder cancer tissues compared with adjacent normal samples. Patients with elevated REG1α exhibited shorter recurrence times and poor survival. Conclusion: Downregulation of REG1α expression can reduce tumor growth, migration, invasion and angiogenesis. Our study demonstrates that REG1α can be used as a marker of recurrence and prognosis in bladder cancer. Therefore, REG1α targeting in bladder cancer patients represents a promising therapeutic strategy.